Computational design of antagonist peptides based on the structure of secreted frizzled-related protein-1 (SFRP1) aiming to inhibit Wnt signaling pathway. Issue 5 (24th March 2022) - Mafakher, Ladan; Rismani, Elham; Rahimi, Hamzeh; Enayatkhani, Maryam; Azadmanesh, Kayhan; Teimoori-Toolabi, Ladan
Abstract: Aberrant activation of Wnt/β-catenin signaling pathway, due to the genetic or epigenetic changes, is responsible for tumorigenesis in epithelial cells of different types of cancer such as colorectal cancer. Secreted Frizzled-Related Protein-1 (SFRP1), as one of the antagonist proteins of this pathway, is hyper-methylated in colorectal cancer leading to the formation of Wnt-Fz-LRP and activation of Wnt/β-catenin signaling pathway. We aimed to design antagonist peptides based on SFRP1 structure against wingless-type 2 (Wnt2), a highly expressed ligand in different cancers like colorectal cancer, to inhibit the formation of the initial triple complex of Wnt-Fz-LRP. After homology modeling of SFRP1, molecular docking showed that Wnt2 and SFRP1 interact in the same mode of xWnt8-mFz8 and hWnt3-mFz8 through the thumb and finger binding sites. These binding sites were selected for designing peptides using either substitution or deep learning-based approaches. The efficiency of each designed peptide in interacting with Wnt2 was evaluated by molecular docking. Stability assessment of Wnt2-peptide complexes via molecular dynamic (MD) revealed that the designed peptides could effectively interact with Wnt2 binding sites during the simulation. However, the designed peptides against the thumb site had higher binding affinity and hydrogen bonds compared to the initial sequence. The secondary structure of the designed peptides indicated an alpha-helix structure which is a favorable structure for peptide drugs. Computing the physicochemical properties of peptides predicted a fairly acceptable structure which made them promising candidates in the treatment of cancers like CRC. AUTHOR SUMMARY: Cancer accounts for the second cause of death in the world. There are different pathways that are activated in cancer which can be considered as drug targets for inhibition. Wnt signaling pathway is one of the most important pathways in cancer. In this study, we studied one of the inhibitors of Wnt signaling pathway as SFRP1 to find inhibitory peptides by mimicking this protein. This pathway is responsible for tumorigenesis in different types of cancer especially colorectal cancer. In this regard, we studied the nature of the complex between SFRP1 and Wnt2 and found two binding sites in Wnt which can be selected for inhibiting this protein. Due to the interaction, we designed peptides for attaching to Wnt2 leading to inhibition of Wnt signaling pathway. The efficiency of these peptides for inhibiting Wnt was studied by molecular docking and molecular dynamics. These peptides can be used as drug candidates for inhabiting this signaling pathway and treating cancer. Communicated by Ramaswamy H. Sarma